OROCLINAL BENDING IN THE CALEDONIDES OF WESTERN IRELAND - Smethurst, M; Macniocaill, C; Ryan, P (1994)
New palaeomagnetic data from the Caledonides of western Ireland indicate that the Silurian rocks of South Mayo underwent oroclinal bending, following folding, in Siluro-Devonian time. Bending was accommodated on faults cutting the Silurian sequence, and was driven by strike slip motion across the Antrim-Galway Line, a recently recognized major curvilinear lineament. The Silurian rocks in the east of the region suffered up to 30° clockwise rotation, increasing towards the west to approximately 70°. This implies that the underlying Dalradian rocks of the Connemara Massif to the south must also have undergone clockwise rotation in late Silurian/early Devonian time. This is consistent with published paleomagnetic data from the Connemara Gabbro and accounts for the swing in strike of the Caledonian orogen in this part of western Ireland. -from Authors